Emotion Regulation Training May Improve Stress, Depression, Anxiety, and Physical Activity. (16th December 2020) - Wierenga, Kelly; Fresco, David; Alder, Megan; Moore, Shirley
Abstract: The purpose of this two-arm randomized controlled pilot study was to assess initial efficacy of the theoretically-based RENEwS intervention, designed to improve emotion regulation and thereby decrease depression and anxiety and increase moderate to vigorous physical activity (MVPA) following a cardiac event. Participants (n=30, 83% men) recruited from cardiac rehabilitation were randomized to five weekly 1-hour sessions of RENEwS intervention or active control. Although this trial was not powered for confirmatory efficacy (p's > .02, but many greater than .05), RENEwS participants evidenced an advantage over Control participants in terms of reductions in stress (Cohen's f = .47), depression symptoms (Cohen's f = .34), anxiety symptoms (Cohen's f = .40) but only modest improvements in MVPA from baseline to 5 months (Cohen's f = .08). Findings support potential efficacy and testing RENEwS in a larger sample.